Prions: Potential Threat to Mankind and Dental Implications - Ajay R Bhoosreddy; AIok A Lathi; Aniket A Lathi (Wolters Kluwer Medknow Publications, 2010)
Prion diseases are fatal, infectious, neurodegenerative disorders with special implications for infection control in the health care system. The causative agent is highly resistant to routine disinfection and sterilization processes and has been transmitted during health care interactions. Thus, it is important to use evidence gained through research and case reports to minimize risk of infection. There is no data suggesting that prions are transmitted easily during dental sittings but there remains a rare risk of such transmission if appropriate infection measures are not adhered to.